Probabilistic PMU Placement in Electric Power Networks: An MILP-Based Multiobjective Model - Aghaei, Jamshid; Baharvandi, Amir; Rabiee, Abdorreza; Akbari, Mohammad-Amin (IEEE transactions on industrial informatics, 2015)
This paper presents a multiobjective probabilistic model for the placement of phasor measurement units (PMUs) in electrical power networks. The proposed model simultaneously optimizes two objectives functions: 1) minimizes the number of PMUs; and 2) maximizes the expected value of system's redundancy (or minimizes the unobservability of the system). Incorporating the impact of zero-injection buses, an efficient formulation is used to evaluate the probability of unobservability of buses resulted from line outages and PMU loss. The extracted formulation is based on the mixed integer linear programming (MILP) framework, which is efficiently solvable by high-performance commercial solvers. This multiobjective optimization problem (MOP) is solved by augmented epsilon-constraint and weighting approach. Accordingly, two new indices are introduced to compare these two multiobjective methods. Finally, the ultimate solution among the Pareto front is recognized using a fuzzy decision-making process. The IEEE 57-bus test system is used to examine the effectiveness of the proposed frameworks.